Effect of constant and intermittent heat stress on rectal temperature and implantation sites in the rat - Sulong, Adnan; Graves, C. N. (Malaysian Society of Applied Biology, 1986)
Mated female rats were exposed to an ambient temperature of 23.0° C (control) or 36.0 ° C (heat treatment) on day 1 to 6 of pregnancy; the latter was either exposed constantly (CHS) or intermittently (lHS) to heat from 1000 to 1500 hr daily. The animals were killed on day 6 of pregnancy and the implantation sites counted. The significant increase in rectal temperature in the hot room indicated that the rats were under heat stress. The acute response on day 1 of exposure to heat showed that there was a significant rapid increase in rectal temperature by the first 30 min postex- posure. Thereafter, the rectal temperature decreased to a lower hyperthermic state, indicating that acclimation has taken place. The number of implantation sites was essentially the same for the control and IHS groups (12.5 vs 12.6). A smaller number of implantation sites (10.5) was observed for the CHS group. In conclusion the study shows that in rats constant exposure to heat stress reduces embryonic survival whereas intermittent exposure has no detrimental effect. This is postulated to be due to the ability of rats to dissipate the heat, gained during exposure to heat stress, to the cooler environment after heat treatment is ceased.